The effects of voice content on stress reactivity: a simulation paradigm of auditory verbal hallucinations - Baumeister, David; Peters, Emmanuelle; Pruessner, Jens; Howes, Oliver D.; Chadwick, Paul (Schizophrenia research, 2022)
Objectives - Psychosis is associated with increased subjective and altered endocrine and autonomic nervous system stress-reactivity. Psychosis patients often experience auditory verbal hallucinations, with negative voice content being particularly associated with distress. The present study developed a voice-simulation paradigm and investigated the effect of simulated voices with neutral and negative content on psychophysiological stress-reactivity, and the effect of mindful voice-appraisals on stress-reactivity. - Method - Eighty-four healthy participants completed the Montreal Imaging Stress Task with simultaneous presentation of one of three randomly allocated auditory stimuli conditions: negative voices, neutral voices or non-voice ambient sounds. Subjective stress-levels and mindful voice-appraisals were assessed using questionnaire measures, and cortisol and α-amylase levels were measured using saliva samples. - Results - ANOVA revealed a significant effect of condition on subjective stress-levels (p=.002), but not cortisol (p=.63) or α-amylase (p=.73). Post-hoc analyses showed that negative voices increased subjective stress-levels relative to neutral voices (p=.002) and ambient sounds (p=.01), which did not differ from each other (p=.41). Mindful voice-appraisals were associated with less distress across conditions (p=.003), although negative voices were also associated with less mindful appraisals (p<.001). - Conclusions - Negative voice content, rather than voices or auditory stimuli per se, is linked to greater subjective but not physiological stress-reactivity. Mindful appraisals may partially moderate this effect. These findings highlight the importance of voice content for the impact of voice-hearing, and highlight the potential value of mindfulness training to treat voice distress in psychosis.